Cari Mora [compact disc, unabridged] - Harris, Thomas, 1940- (Hachette Audio, 2019)
A ruthless man driven by unspeakable appetites to pursue a fortune in cartel gold hidden beneath a Miami mansion finds his efforts challenged by Cari Mora, the mansion's caretaker and a war survivor with unusual talents.